How do you multiply (-1-5i)(3-6i) (15i)(36i) in trigonometric form?

1 Answer
Jun 14, 2018

color(crimson)((-1-i5) (3 - i 6) = (-33 - i 9)(1i5)(3i6)=(33i9)

Explanation:

z_1 = (-1 - i 5) z1=(1i5)

r_1 = sqrt(1^2 + 5^2) = sqrt26r1=12+52=26

theta_1 = arctan (-5/-1) = arctan 5 = 258.69^@, " III Quadrant"θ1=arctan(51)=arctan5=258.69, III Quadrant

z_2 = (3 - i 6)z2=(3i6)

r_2 = sqrt(3^2 + 6^2) = sqrt45r2=32+62=45

theta_2 = -6/3 = - 2 = 296.57^@, " IV Quadrant"θ2=63=2=296.57, IV Quadrant

z_1 * z_2 = (r_1 * r_2) * (cos (theta-1 + theta_2) + i sin (theta_1 + theta_2))z1z2=(r1r2)(cos(θ1+θ2)+isin(θ1+θ2))

z_1 * z_2 = (sqrt 26 * sqrt 45) * (cos (258.69 + 296.57) + i sin(258.69 + 296.57))z1z2=(2645)(cos(258.69+296.57)+isin(258.69+296.57))

=> 34.21 (cos 555.26 + i sin 555.26) = 34.21(-0.9647 - i 0.2632)34.21(cos555.26+isin555.26)=34.21(0.9647i0.2632)

color(crimson)((-1-i5) (3 - i 6) = (-33 - i 9)(1i5)(3i6)=(33i9)